Membrane pressures predict clotting of pediatric continuous renal replacement therapy circuits - Kakajiwala, Aadil; Jemielita, Thomas; Hughes, John Z.; Windt, Kimberly; Denburg, Michelle; Goldstein, Stuart L.; Laskin, Benjamin (Pediatric nephrology (Berlin, West), 2017)
Background Clotting of continuous renal replacement therapy (CRRT) circuits leads to inadequate clearance, decreased ultrafiltration, and increased resource use. We identified factors associated with premature clotting of circuits during CRRT in children. Methods In a retrospective cohort of 26 children (median age 11.8 years) receiving 79 CRRT circuits (51 heparin, 22 citrate, 6 using no anticoagulation), we captured hourly pressure, flow, and fluid removal rates along with all activated clotting time (ACT) and circuit ionized calcium measurements. Cox and logistic regression models were used to examine factors associated with premature circuit clotting before the scheduled 3-day circuit change. Results Of the 79 circuits, 51 (64.6%) underwent unplanned filter change due to filter clotting (median duration 18.25 h, interquartile range [IQR] 9.25, 33.5 h), and 28 (35.4%) underwent scheduled change (median duration 66 h, IQR 61.00, 69.00 h). Patient age, catheter size and location, blood flow rate, and the percentage of pre-filter replacement fluid were not associated with premature clotting. Heparin circuits were less likely than citrate circuits to clot prematurely. Each 1-mmHg increase in the transmembrane or filter pressure was independently associated with a 1.5% (95% confidence interval [CI] 1.0–2.0%) and 1.5% (95% CI 1.0–2.0%) higher risk of clotting, respectively. Higher ACTs were associated with lower transmembrane ( p = 0.03) and filter ( p < 0.001) pressures. Conclusions The majority of circuits in our cohort were subject to unplanned filter changes. Elevated transmembrane and filter pressures were associated with clotting. Our results suggest that maintaining higher ACT may decrease the risk of circuit clotting. Larger studies are needed to examine other factors that may prolong the lifespan of the CRRT circuit in this high-risk population.